2021
DOI: 10.3390/soilsystems5010017
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Alters Permafrost Soil Redox Conditions, but Meta-Omics Show Divergent Microbial Community Responses by Tundra Type in the Arctic

Abstract: Soil anoxia is common in the annually thawed surface (‘active’) layer of permafrost soils, particularly when soils are saturated, and supports anaerobic microbial metabolism and methane (CH4) production. Rainfall contributes to soil saturation, but can also introduce oxygen, causing soil oxidation and altering anoxic conditions. We simulated a rainfall event in soil mesocosms from two dominant tundra types, tussock tundra and wet sedge tundra, to test the impacts of rainfall-induced soil oxidation on microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 114 publications
(163 reference statements)
1
5
0
Order By: Relevance
“…The relative abundance of archaeal taxa was <3% at any given site or depth (Figure 3, Figure S2) but still differed statistically between tundra types (ANOVA; p < 0.001). Archaeal taxa consisted primarily of methanogenic Euryarchaeota such as Methanobacteriales and Methanosarcinales, consistent with similar observations across the tundra region (Deng et al, 2015;Hultman et al, 2015;Lipson et al, 2013;Romanowicz et al, 2021;Tripathi et al, 2018).…”
Section: Notesupporting
confidence: 85%
See 2 more Smart Citations
“…The relative abundance of archaeal taxa was <3% at any given site or depth (Figure 3, Figure S2) but still differed statistically between tundra types (ANOVA; p < 0.001). Archaeal taxa consisted primarily of methanogenic Euryarchaeota such as Methanobacteriales and Methanosarcinales, consistent with similar observations across the tundra region (Deng et al, 2015;Hultman et al, 2015;Lipson et al, 2013;Romanowicz et al, 2021;Tripathi et al, 2018).…”
Section: Notesupporting
confidence: 85%
“…The higher abundance of Pseudomonadota in the active layer could be related to their preference for higher concentrations of nutrients (Kim et al, 2016 ), especially given that the relative abundance of Alphaproteobacteria and Gammaproteobacteria taxa were shown to increase after fertilization compared with control plots at Toolik (Campbell et al, 2010 ; Koyama et al, 2014 ). Also, the greater abundance of bacterial taxa such as Geobacterales (Desulfobacterota) in the active‐layer microbiome of WS tundra (Table 1 ) is likely because they thrive under saturated conditions common in the active layer of WS tundra (Emerson et al, 2015 ), as has been previously reported from the Toolik Lake region (Romanowicz et al, 2021 ). This suggests that the depth‐dependent variations in the soil microbiome could be related to the different resource needs of each bacterial taxon.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Species from this genus are frequently the most abundant methanogens in methanogenic terrestrial environments such as natural wetlands and flooded rice paddy soils and in many anaerobic digester systems (2)(3)(4)(5)(6)(7)(8). Methanothrix species are also important members of the methanogenic community in Arctic and Antarctic sediments (9)(10)(11), and scientists are particularly concerned with increases in methane production linked to melting permafrost in these polar terrestrial sediments as this will lead to a positive feedback loop that will further exacerbate climate change (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the datasets from rhizosphere soils were not used in this study because they are extensively and dynamically affected by the plant roots (Zhalnina et al, 2018) and not representative of the soil microbial communities. In total, we collected 1445 datasets as listed in Table S1 (Angle et al, 2017; Bahram et al, 2018; Berkelmann et al, 2020; Black and Just, 2018; Cania et al, 2019; Cha et al, 2021; Chen et al, 2019; Chu et al, 2018; Crits-Christoph et al, 2018; Hartman et al, 2017; Huber et al, 2018; Jiang et al, 2018; Johnston et al, 2016; Li et al, 2018, 2020; Links et al, 2021; Liu et al, 2018; Ma et al, 2018; Neal et al, 2021; Nelkner et al, 2019; Orellana et al, 2018; Ouyang and Norton, 2020; Paungfoo-Lonhienne et al, 2017; Romanowicz et al, 2021; Sukhum et al, 2021; Suttner et al, 2020; Hang Wang et al, 2021; Wang et al, 2020; Woodcroft et al, 2018; Wu et al, 2021; Xiao et al, 2016; Xue et al, 2019; Yu et al, 2019; Yurgel et al, 2019; Zhang et al, 2019; Zheng et al, 2021). The latitude and longitude of each sampling site were obtained from public databases [INSDC BioSamples database (Courtot et al, 2022) and MG-RAST] and verified with the descriptions in each publication.…”
Section: Methodsmentioning
confidence: 99%